QTL analysis, association mapping and marker-assisted selection for some quality traits in bread wheat - An overview of the work done at CCS University, Meerut - Gupta, P K; Balyan, H S; Mir, R R; Kumar, J; Kumar, A; Kumar, S; Jaiswal, V; Tyagi, S; Kumari, S (Journal of Cereal Research, 2011)
The present article summarises the results of our studies involving QTL mapping and marker-assisted selection (MAS) for three quality traits in bread wheat undertaken during the last more than a decade; however, most of these results were earlier published. The three quality traits include pre-harvest sprouting tolerance (PHST), grain protein content (GPC), and grain weight (GW). For PHST, a total of 13 QTLs were identified using two RIL populations and 30 QTLs were identified through association mapping, six QTLs being common in the two approaches (interval mapping and association mapping). Meta-QTL analysis for PHST was also conducted for 4 chromosomes (3A, 3B, 3D, 4A) and 8 meta-QTLs representing 36 earlier reported QTLs were identified. For GPC, a total of 13 QTLs were identified using interval mapping, but no association mapping was attempted. Similarly for GW, 10 QTLs were identified through interval mapping and 25 QTLs were identified through association mapping, four of these QTLs being common in both the approaches. MAS was also attempted for all the three traits. For PHST, seven BC3F4 progenies with high level of PHST were developed [these PHS tolerant lines also carried two Lr genes (Lr24 and Lr28) earlier introgressed through MAS]. For GPC, seven MAS-derived progenies (carrying the major gene Gpc-B1) with significantly higher GPC (14.83% to 17.85%) than their recipient parental genotypes were selected. Similarly for GW, 13 MAS-derived BC3F2 plants carrying different QTL combinations and having 1000 grain weight higher than that of the donor parent RS111 were selected. The results of these studies demonstrated successful tagging/mapping of QTL through QTL interval/association mapping and their subsequent use in marker-aided selection for wheat improvement.